Case Report: Oral fecal microbiota transplantation in a Mediterranean spur-thighed tortoise (Testudo graeca) suffering from chronic gastrointestinal disease—procedure, clinical outcome and follow-up - Hetterich, Johannes; Pees, Michael (Frontiers in Veterinary Science, 2025)
IntroductionFecal microbiota transplantation (FMT) is the process of transferring fecal microbiota from a healthy donor into the gastrointestinal tract of a recipient. Although many mechanisms of FMT are still not completely understood at present, it has been described that the treatment of various gastrointestinal diseases in different species, including humans, is significantly improved by FMT therapy. Since the first report on FMT therapy in veterinary medicine in small mammals numerous cases have been reported, but little information has been published on the therapeutic effects of FMT treatment in reptiles. The present case report describes the effects of orally administered fecal microbiota transplantation in a Mediterranean spur-thighed tortoise (Testudo graeca) suffering from chronic gastrointestinal disorders.Case presentationA nine-year-old, 330 g, intact female Mediterranean spur-thighed tortoise (Testudo graeca) from the animal owner’s own offspring was presented for consultation due to decreased general condition, anorexia and sialorrhea following oral intake of a lettuce species (Lactuca virosa) known for its poisonous plant ingredients (sesquiterpene lactones) 3 weeks prior to presentation. Pre-existing conditions were not reported. Clinical examination revealed sialorrhea and a reduced general condition. Diagnostic procedures included blood chemistry, radiography and ultrasonography. Despite repeated treatment attempts with various medical regimes over 158 days, the tortoise continued showing variable recurring gastrointestinal symptoms. An orally administered FMT was initiated and continued for a total of 3 weeks. Gastrointestinal signs improved rapidly within 1 week and resolved completely after 3 weeks. Over a follow up period of 9 months, no symptom recurrence or adverse effects were monitored.ConclusionThis case report describes the first successful trial of fecal microbiota transplantation in chelonians. The outcome indicates that this therapeutic approach may be beneficial not only to small animals but also for the therapy of gastrointestinal disorders in reptiles, especially those cases with insufficient conventional therapy results.